Features of surgical treatment of the apical right lung cancer - E. A. Epifantsev; V. Yu. Gritsun; S. V. Deryabin; Yu. V. Ivanov (Исследования и практика в медицине, 2022)
The tumor of the upper sulcus of the lung is an atypical form of cancer, which is characterized by invasion into the aperture of the chest and mediastinum, which in turn determines the manifestation of the disease of neurological symptoms.Tactical approaches in the treatment of this disease are well known. To date, complex treatment is used, which includes neoadjuvant chemoradiotherapy followed by surgical treatment. This approach gives the best result in terms of prognosis and survival of patients.Considering the local invasion, planning the surgical stage in the treatment of this group of patients is a difficult task and requires a multidisciplinary approach to determine the optimal surgical tactics.This paper presents our own clinical observation of the successful surgical treatment of a 54‑year‑old patient with a tumor of the upper sulcus of the right lung. In order to adequately visualize the pathological process, safety and convenience of surgical intervention, Hemi‑Clamshell access was used, which combined the advantages of sternotomy and thoracotomy. Taking into account the topical location of the tumor, the greatest technical difficulties during the operation arose when performing mobilization of the upper lobe of the right lung, adequate lymph dissection near large arterial and venous vessels, removal of part of the chest wall of the pleural cavity dome.Also, one of the important issues when planning surgical treatment of this group of patients is to determine the indications for restoring the skeletal function of the chest after rib resection. In our case, despite the resection of the posterior segments of the I–III ribs, all the muscles of the anterior chest wall were preserved, which took over part of the skeletal function of the chest. There was no development of paradoxical breathing in the postoperative period.Surgical interventions of this amount should be performed in specialized thoracic oncology clinics and multidisciplinary medical institutions. At the same time, a multidisciplinary approach of doctors of various specialties, the experience of the operating team in performing such operations and the appropriate anesthesiological and resuscitation service is needed.